Forecasting Earthquake-induced Ground Movement under Seismic Activity Using Response Surface - Kennedy C. Onyelowe; Denise‐Penelope N. Kontoni; Fortune K. C. Onyelowe; Viroon Kamchoom‬; Shadi Hanandeh; Ahmed M. Ebid; Néstor Ulloa; Arif Ali Baig Moghal; M. Vishnupriyan (Sustainable Intelligent Infrastructure, 2025)
This study employs Response Surface Methodology (RSM) to model and optimize earthquake-induced ground movements in gravelly geohazard-prone environments. RSM efficiently evaluates the interactions of seismic parameters, including soil type, fault distance, and peak ground acceleration (PGA), reducing computational and experimental efforts. A dataset of 234 entries encompassing 11 seismic and soil stress variables was curated and analyzed, yielding a high-precision predictive model with an R² of 0.9997. The resulting closed-form equation facilitates accurate risk assessment, structural safety optimization, and seismic resilience planning. By identifying critical thresholds and nonlinear relationships, RSM supports cost-effective mitigation strategies, infrastructure design, and retrofitting in earthquake-prone regions.
Keywords: Structural Health Monitoring Techniques; Seismic Performance and Analysis; Landslides and related hazards